GOVERNMENT READINESS FOR FLEXIBLE WORKING: MANAGING WORK-FROM-HOME POLICY FOR CIVIL SERVANTS IN INDONESIA - Sugiyarto, Yusuf; Maulana, Naufal Bahri; Syam, Teungku Muhammad Ja’far Ali (CosmoGov: Jurnal Ilmu Pemerintahan, 2026)
The work-from-home policy for civil servants in Indonesia has shifted from a pandemic emergency response to becoming part of a transformation in work culture, mobility efficiency, energy savings, bureaucratic digitalisation, and the strengthening of output-based performance. This shift raises important questions regarding the readiness of government organisation management to implement WFH in a productive, accountable manner that remains focused on public service. This study aims to analyse management readiness in the implementation of the civil service work-from-home policy in Indonesia. It employs a qualitative approach through document analysis, media content analysis, and preliminary bibliometric mapping of regulations, government documents, media, academic literature, and selected international comparative documents based on their relevance to civil service work-from-home and public sector management readiness. The analysis utilises the Armenakis, Harris, and Mossholder Readiness Model and the AMO Framework. The findings indicate that Indonesia possesses a relatively strong foundation of need for change and regulatory support; however, implementation readiness remains a work in progress due to challenges regarding job classification, digital readiness, remote supervision, output-based performance indicators, and service continuity. This study offers a novel perspective by framing WFH for civil servants as an issue of managerial readiness, rather than merely workplace flexibility, and provides implications for strengthening the design of flexible working arrangements in the public sector